A metacognitive learning environment for physical science classrooms - Hanekom, Heidi (University of the Free State, 2017)
In order to address the problem of poor Physical Sciences performances in the Northern Cape, metacognitive awareness was identified as being the impetus that could stimulate Physical Sciences learning and improve performances in the subject. A metacognitive learning environment was identified as being a possible factor that could improve learners’ metacognitive awareness. The aim of the research was to determine to what extent the Physical Sciences learning environments in the Northern Cape afforded learners the opportunity to develop metacognitive awareness. This was done by first investigating the knowledge and skills learners need to master in Physical Sciences. Metacognition was identified as playing a role in acquiring knowledge and skills in Physical Sciences. The need for metacognitive awareness in Physical Sciences learning was highlighted by analysing how Physical Sciences learning takes places. Existing research into the components of metacognition was reviewed and when the components were analysed with reference to Physical Sciences learning, the importance of metacognitive awareness in effective Physical Sciences learning was established. The metacognitive learning environment was identified as a factor that could improve learners’ metacognitive awareness and existing research into metacognitive learning environments were reviewed and applied to Physical Sciences classrooms. Learners’ metacognitive awareness in Physical Sciences classrooms in the Northern Cape was investigated as well as the difference between learners’ metacognitive awareness in Dinaledi schools and non-Dinaledi schools. The characteristics of Northern Cape learning environments that are structured for Physical Sciences were identified and the difference between Physical Sciences learning environments in Dinaledi schools and non-Dinaledi schools was explored. A positive correlation between learners’ metacognitive awareness in Physical Sciences and their Physical Sciences learning environments was confirmed. It was found, however, that the Physical Sciences learning environments did not always provide learners with the opportunity to develop their metacognitive awareness. Recommendations were made as to how the learning environments could be structured to allow for metacognitive awareness development in Physical Sciences.

Ten einde die probleem van swak leerderuitslae in Fisiese Wetenskappe in die Noord-Kaap aan te spreek, is metakognitiewe bewussyn geïdentifiseer as die hoofdryfveer wat leer in Fisiese Wetenskappe kan stimuleer en uitslae in die vak kan verbeter. ŉ Metakognitiewe leeromgewing is as moontlike faktor wat leerders se metakognitiewe bewussuyn kan verbeter geïdentifiseer. Die doel van die navorsing was om te bepaal tot watter mate Fisiese Wetenskappe-leeromgewings in die Noord-Kaap aan leerders die geleentheid gebied het om metakognitiewe bewussyn te ontwikkel. Dit is gedoen deur, eerstens, die kennis en vaardighede wat leerders benodig om Fisiese Wetenskappe te bemeester te ondersoek. Metakognisie is geïdentifiseer as ŉ faktor in die verkryging van kennis en vaardighede in Fisiese Wetenskappe. Die behoefte vir metakognitiewe bewussyn in Fisiese Wetenskappe-leer is uitgelig deur hoe leer in Fisiese Wetenskappe plaasvind te analiseer. Bestaande navorsing oor die komponente van metakognisie is daarna ondersoek en by die analise van die komponente met verwysing na Fisiese Wetenskappe-leer is die belangrikheid van metakognitiewe bewussyn vir doeltreffende Fisiese Wetenskappe-leer vasgestel. Die metakognitiewe leeromgewing is daarna geïdentifiseer as ŉ faktor wat leerders se metakognitiewe bewussyn kan verbeter en bestaande navorsing oor metakognitiewe leeromgewings is ondersoek en toegepas op Fisiese Wetenskappe-klaskamers. Leerders se metakognitiewe bewussyn in Fisiese Wetenskappe-klaskamers in die Noord-Kaap is ondersoek asook die verskil tussen leerders se metakognitiewe bewyssyn in Dinaledi-skole en nie-Dinaledi skole. Die eienskappe van Noord-Kaapse leeromgewings wat gestruktureer is vir Fisiese Wetenskappe is geïdentifiseer en die verskil tussen Fisiese Wetenskappe-leeromgewings by Dinaledi-skole en nie-Dinaledi skole is verken. ‘n Positiewe korrelasie tussen leerders se metakognitiewe bewussyn in Fisiese Wetenskappe en hul Fisiese Wetenskappe-leeromgewings is bevestig. Dit is bevind dat die Fisiese Wetenskappe leeromgewings nie altyd aan leerders die geleentheid gegun het om hul metakognitiewe bewussyn te ontwikkel nie. Voorstelle is ontwikkel oor hoe die leeromgewings gestruktureer kan word om metakognitiewe bewussynsontwikkeling in Fisiese Wetenskappe te bevorder.
Dissertation (M.Ed. (Curriculum Studies))--University of the Free State, 2017
Keywords: Metacognition; Cognitive learning; Physical sciences -- Study and teaching -- South Africa -- Northern Cape